Scientific evidence on nursing care for patients diagnosed with stroke in the Intensive Care Unit (Research, Society and Development, 2021)
Analyze the scientific evidence on nursing care for patients diagnosed with stroke in the Intensive care unit. This study deals with a bibliographic review of the integrative literature review method, carried out in the months of October and November 2020. The search was carried out, VHL, using the databases LILACS, BDENF, SCIELO, and through the Google Portal Academic, adhering to the descriptors: “Nursing care” AND “Stroke” AND “ICU”, crossed with the operator by booluding “AND”. The nurse is highlighted as the professional who has the greatest contact with the patient, therefore, he is responsible for most of the care and procedures performed. This professional works with the purpose of reducing the sequels caused by the disease and develops assistance focused on the mental, spiritual and physical state. The nurse is the most qualified professional, either because of the holistic nature of his education, or because of the simple and indisputable fact of being present for a longer time in patient care. In this way, the nursing guidelines for the companion / family member should include from more general aspects, related to the hospital dynamics to facilitate their adaptation to the environment, to more specific explanations about the equipment used and procedures to which the patients are submitted.